2012
DOI: 10.1016/j.rbmo.2012.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Array CGH analysis shows that aneuploidy is not related to the number of embryos generated

Abstract: This study retrospectively analysed array comparative genomic hybridization (CGH) results of 7753 embryos from 990 patients to determine the frequency of embryonic euploidy and its relationship with the cohort size (i.e. the number of embryos available for biopsy and array CGH analysis). Linear regression analysis was performed to assess the effect of cohort size on euploidy rate adjusted for the effect of female age. While increasing female age was associated with a significant decrease in euploidy rate of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
129
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(155 citation statements)
references
References 24 publications
17
129
0
5
Order By: Relevance
“…Previously published data from the same database presented here demonstrated that the overall cohort size was unrelated to aneuploidy rate [36]. Thus, the odds of having at least one euploid blastocyst increased with every additional blastocyst available for PGS.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Previously published data from the same database presented here demonstrated that the overall cohort size was unrelated to aneuploidy rate [36]. Thus, the odds of having at least one euploid blastocyst increased with every additional blastocyst available for PGS.…”
Section: Discussionsupporting
confidence: 53%
“…At least one center was included from the following locations: California, Nevada, Oregon, Illinois, Florida, Georgia, Pennsylvania, New York, Massachusetts, and Canada. Of note, this database has been utilized to previously report PGS data from Reprogenetics [36,22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cochrane review of 12 randomized controlled trials demonstrated that live birth rates can be optimized by performing blastocyst transfer compared to cleavage stage embryo transfers [9]. In addition, a recent study found chromosome abnormalities were reduced at the blastocyst stage compared to the cleavage embryo stage [10].…”
Section: Introductionmentioning
confidence: 99%
“…A recent Cochrane review found that blastocyst ET has a statistically significant higher live birth rate than cleavage stage ET, 32-42 vs 31 % respectively [7]. Furthermore, longer cell culture allows for improved selection of higher grade embryos and decreases the rate of aneuploidy [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%